THE INFLUENCE MEDIA OF LEARNING BASED MACROMEDIA FLASH TO KNOWLEDGE ABOUT TAX ON STUDENT SMA SIDOARJO - Yuni Purnama Sari (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
The purpose of this study was to determine the effect of learning media based of macromedia flash on the knowledge of students high school in Sidoarjo Regency. The type of research carried out was quasi-experimental. The study was designed with two treatment classes, namely the experimental class and the control class. The sample used as subjects in this study were two high schools in Sidoarjo Regency, East Java. The research subjects are class XI PGRI High School and Sidoarjo High School. Each school was chosen by two classes which were used as the experimental class and the control class. The research instrument used was a test instrument about tax material. The research data were analyzed using the parametric statistical test with a t-test that aims to determine the average difference of each class of research. The results showed that: there was a significant difference between the knowledge of students who were given learning assisted by interactive media based on macromedia flash tax and conventional learning. Results of t-test analysis show that the significance value is less than alpha 0.05.